2021
DOI: 10.1111/jcmm.16542
|View full text |Cite
|
Sign up to set email alerts
|

mGPDH Deficiency leads to melanoma metastasis via induced NRF2

Abstract: Melanoma, which is also known as malignant melanoma, is among the most aggressive forms of skin cancer and has a poor cure rate due to its invasive nature. 1,2 Melanoma mostly develops from pigment-containing cells known as melanocytes and thus predominantly a disease of the skin but can also occur at mucous membranes and other sites. 3 With treatment, in the United States, the 5-year survival rate is 65% among

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…There is evidence that Nrf2 activation enhances cancer cell metastasis in melanoma, suggesting that Nrf2 has an onco-promoter role [ 34 , 47 , 59 ]. In fact, as long as the cell is intact, Nrf2 and its lower genes try to save the cell from becoming cancerous by reducing oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is evidence that Nrf2 activation enhances cancer cell metastasis in melanoma, suggesting that Nrf2 has an onco-promoter role [ 34 , 47 , 59 ]. In fact, as long as the cell is intact, Nrf2 and its lower genes try to save the cell from becoming cancerous by reducing oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al showed that in A375 melanoma cells, knocking down mGPDH activates the Nrf2 pathway, causing melanoma cell metastasis, whereas co-inhibiting Nrf2 prevents melanoma cell metastasis in vivo and in vitro. These findings show that via inhibiting the Nrf2 signaling pathway, mGDPH suppresses melanoma cell motility and invasion [ 47 ]. P62, an autophagy-degrading factor, is overexpressed in malignant and metastatic melanomas regardless of BRAF/NRAS mutant status.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intermittent hypoxia promoted melanoma lung metastasis through oxidative stress in a mouse model of obstructive sleep apnea ( 46 ). Mitochondrial glycerol-3-phosphate dehydrogenase (mGPDH) inhibits melanoma migration, and invasion by suppressing NRF2 and downstream oxidative signals ( 47 ). Our study demonstrates for the first time that NRF2, as a transcription factor, can regulate the transcription of PRPS1, an important enzyme in nucleotide metabolism.…”
Section: Discussionmentioning
confidence: 99%